PELAKSANAAN DIVERSIFIKASI PRODUK DALAM RANGKA MENINGKATKAN VOLUME EKSPOR (Studi Kasus Perusahaan Batik Ayu di Kota Pekalongan) - Nurul Hidayah Indah; Suharyono Suharyono; Sunarti Sunarti (Jurnal Administrasi Bisnis, 2017)
The textile industry is one of the leading industries of Indonesia, both in the domestic trade and international trade. Indonesian textile products of the flagship and pride of Indonesian batik. The purpose of this study: 1) To investigate the implementation of product diversification strategy and 2) To determine the impact of product diversification strategy to increase the export volume in the Company batik Ayu. This type of research used in this study is a qualitative study using a descriptive approach. The focus of research is on the company's product diversification strategy batik Ayu and the impact of product diversification strategy.The analysis showed that the attempt was first made by the owner is doing batik training for local people, finally in 2004 the owners founded the company Batik Cap "Ratu Ayu". Some of the uniqueness of the Company Batik Cap "Ratu Ayu", the first characteristic, seen from manufacturing techniques, different from Pekalongan batik, fabric manufacturing techniques are sewed into clothes first and then dibatik. so motifs or motif connect from the front to the rear. Secondly, in terms of coloring. The method used by the Company Batik Cap "Ratu Ayu" Pekalongan is, the first following the exhibitions. Batik adding some pattern every years in kain panjang product, hem, blus, sarung and sprei to increase export volume in 2011 until 2014. Keywords: Diversification and Export Volume Increases ABSTRAK Industri tekstil merupakan salah satu industri terkemuka di Indonesia. Baik dalam pasar nasional maupun pasar internasional produk batik merupakan kebanggaan dari produksi tekstil Indonesia. Tujuan  dari penelitian ini: 1) Untuk mengetahui pelaksanaan diversifikasi produk dan 2) Untuk mengetahui pengaruh dari pelaksanaan diversifikasi produk pada perusahaan batik Ayu. Penelitian ini adalah penelitian kualitatif menggunakan deskriptif. Fokus pada penelitian ini adalah pelaksanaan diverisifikasi produk dalam rangka meningkatkan volume ekspor dan pengaruhnya terhadap volume ekspor dalam perusahaan batik Ayu. Hasil penelitian menunjukkan bahwa pada tahun 2004 pemilik Batik Cap "Ratu Ayu" memberanikan diri untuk membuka usaha ini. Perusahaan batik ini mempunyai beberapa keunikan. Karakteristik yang pertama, dilihat dari teknik pembuatannya, kain yang pada awalnya dibuat motif dan kemudian dijahit sesuai dengan modelnya. Batik Ayu menambah berbagai macam motif setiap tahun baik dalam produksi kain panjang, hem, blus, sarung dan sprei dan dapat meningkatkan volume ekspor ditahun 2011 sampai dengan 2014. Kata kunci : Diversifikasi, peningkatan volume ekspor